Vasotocin and isotocin regulate aquaporin 1 function in the sea bream - Martos-Sitcha, Juan Antonio; Campinho, Marco António; Miguel Mancera, Juan; Martinez-Rodriguez, Gonzalo; Fuentes, Juan (Journal of Experimental Biology, 2015)
Aquaporins (AQPs) are specific transmembrane water channels with an important function in water homeostasis. In terrestrial vertebrates, AQP2 function is regulated by vasopressin (AVP) to accomplish key functions in osmoregulation. The endocrine control of aquaporin function in teleosts remains little studied. Therefore, in this study we investigated the regulatory role of vasotocin (AVTR) and isotocin (ITR) receptors in Aqp1 paralog gene function in the teleost gilthead sea bream (Sparus aurata). The complete coding regions of Aqp1a, Aqp1b, AVTR V1a2-type, AVTR V2-type and ITR from sea bream were isolated. A Xenopus oocyte-swelling assay was used to functionally characterize AQP1 function and regulation by AVT and IT through their cognate receptors. Microinjection of oocytes with Aqp1b mRNA revealed regulation of water transport via PKA (IBMX+forskolin sensitive), whereas Aqp1a mRNA injection had the same effect via PKC signaling (PDBU sensitive). In the absence of expressed receptors, AVT and IT (10(-8) mol l(-1)) were unable to modify AQP1 function. AVT regulated AQP1a and AQP1b function only when the AVTR V2-type was co-expressed. IT regulated AQP1a function, but not AQP1b, only when ITR was present. Considering that Aqp1a and Aqp1b gene expression in the sea bream intestine is highly salinity dependent in vivo, our results in ovo demonstrate a regulatory role for AVT and IT in AQP1 function in the sea bream in the processing of intestinal fluid to achieve osmoregulation. Ministry of Education (Spain) [FPU AP2008-01194]; Portuguese National Science Foundation [SFRH/BPD/66808/2009]; Ministry of Science and Education, Spain [AGL2010-14876]; National Science Foundation (FCT, Portugal) [PTDC/MAR-BIO/3811/2012]